To err is human but to persist is diabolical: Toward a theory of interactional policing - Stivers, Tanya; Chalfoun, Andrew; Rossi, Giovanni (Frontiers in Sociology, 2024)
Social interaction is organized around norms and preferences that guide our construction of actions and our interpretation of those of others, creating a reflexive moral order. Sociological theory suggests two possibilities for the type of moral order that underlies the policing of interactional norm and preference violations: a morality that focuses on the nature of violations themselves and a morality that focuses on the positioning of actors as they maintain their conduct's comprehensibility, even when they depart from norms and preferences. We find that actors are more likely to reproach interactional violations for which an account is not provided by the transgressor, and that actors weakly reproach or let pass first offenses while more strongly policing violators who persist in bad behavior. Based on these findings, we outline a theory of interactional policing that rests not on the nature of the violation but rather on actors' moral positioning.